P3.372 Systematic Review and Meta-Analysis of L1-VLP-based Human Papillomavirus Vaccine Efficacy Against Anogenital Pre-Cancer in Women with Evidence of Prior HPV Exposure. (13th July 2013) - Miltz, A; Price, H; Shahmanesh, M; Copas, A; Gilson, R
Abstract : Background: It is unclear whether L1-VLP-based human papillomavirus (HPV) vaccines are efficacious in preventing anogenital pre-cancer in women with prior vaccine-type HPV exposure. Participants in the phase III efficacy trials were not excluded if infected at baseline (HPV-DNA and serology were performed in retrospect); the efficacy in this sub-group of vaccinees can be derived from published reports. Methods: A systematic review and meta-analysis was conducted to compare the efficacy of L1-VLP-based HPV vaccines with control (hepatitis A or placebo). Randomized-controlled trials (including post-RCT follow-on cohort studies) were identified from MEDLINE, Embase, Web of Science SM, PubMed, Cochrane (and quoted references). Three vaccines were evaluated: Cervarix ™ containing HPV-16/18 VLPs (GSK), Gardasil ® containing HPV-6/11/16/18 VLPs (Merck), and an HPV-16 monovalent vaccine (Merck Research Laboratories). Results: Three RCT reports and one post-RCT follow-on study met the eligibility criteria, comprising data from 13, 339 women who were included in the vaccine studies but had evidence of HPV infection at baseline. Efficacy data were synthesised using a DerSimonian and Laird weighted random-effect model. The mean odds ratio (OR) and 95% confidence interval (CI) for the association between Cervarix ™, Gardasil ® and HPV-16 monovalent vaccine and HPV-associated cervical intraepithelial neoplasia grade 3 or worse (CIN3+) was 0·90 (CI: 0·56, 1·44) and for the association between Gardasil ® and HPV-associated vulval/vaginal intraepithelial neoplasia grades 2–3 (VIN2–3/VaIN2–3) OR 1·20 (CI: 0·07, 20·40). Conclusion: There was no evidence that the HPV vaccines are effective in preventing vaccine-type HPV-associated pre-cancer in women with evidence of prior HPV exposure in this analysis. However, these studies were not designed to investigate the efficacy in this group, so statistical power (sample size, follow-up period and event rate) was insufficient to detect a small effect size. Longer follow-up is also needed to detect possible prevention of re-infection.